The Role of Service Quality, Service Innovation, and Customer Orientation on Service Management Performance through Customer Satisfaction - Aang Gunawan; Yuliantini Yuliantini; Muhammad Thamrin; Olfebri Olfebri; Basri Fahriza (Dinasti International Journal of Education Management and Social Science, 2026)
This study aims to examine the influence of service quality, service innovation, and customer orientation on service management performance through customer satisfaction in service companies in Indonesia. In an increasingly competitive service industry, companies are required to manage their services effectively in order to improve customer satisfaction and strengthen sustainable service management performance. Therefore, understanding the factors that influence service management performance is crucial for service companies in formulating effective service strategies. This research uses a descriptive qualitative approach with a literature review method. The data used are secondary data, consisting of 30 scientific articles obtained from reputable national and international journals. The sources of the articles include international publishers such as Sage, Springer, Elsevier, Web of Science, and Emerald; international databases such as Ebsco, Copernicus, and Google Scholar; as well as reputable national journals indexed in Sinta. The results of the study indicate that service quality, service innovation, and customer orientation have a positive influence on customer satisfaction. In addition, service quality, service innovation, and customer orientation also directly influence service management performance. Customer satisfaction itself has a significant effect on service management performance. Furthermore, customer satisfaction acts as a mediating variable that strengthens the influence of service quality, service innovation, and customer orientation on service management performance in service companies.